Ultrasound evaluation of the patellar tendon and Achilles tendon and its association with future pain in distance runners. Issue 4 (2nd October 2021) - Cushman, Daniel M; Petrin, Ziva; Eby, Sarah; Clements, Nathan D.; Haight, Peter; Snitily, Brian; Teramoto, Masaru
ABSTRACT: Objectives : To examine whether asymptomatic ultrasonographic abnormalities in the Achilles and patellar tendons in runners are associated with an increased risk of pain development. Methods : This is a longitudinal, prospective cohort study with 139 runners recruited at a half and full marathon race. Ultrasound examination of the Achilles and patellar tendons was performed bilaterally the day prior to the race. Self-reported injury data were collected at 1, 3, 6 and 12 months. 104 (74.8%) runners were included in the data analysis. Results : Ultrasonographic tendon abnormalities were found in 24.1% of the Achilles and in 23.1% of the patellar tendons prior to the race. Runners with tendon abnormality were 2–3 times more likely to develop pain within 12 months than those without (relative risk = 3.14, p = 0.010 for Achilles; relative risk = 2.52, p = 0.008 for patellar tendon). After adjusting for gender, age, years of running, average miles per week of running over a year, and pre-race pain, runners with ultrasound abnormality were about 3 times (hazard ratio = 2.89, p = 0.039 for Achilles; hazard ratio = 2.73, p = 0.030 for patellar tendon) more likely to develop pain after the race. Tendon delamination was most strongly associated with pain in both the Achilles (relative risk = 6.00; p = 0.001) and patellar tendons (relative risk = 3.81; p = 0.001). Conclusions : Structural changes in asymptomatic tendons were found in almost 25% of runners. Presence of structural changes was associated with increased development of Achilles and patellar tendon pain within one year.